A Multimodal Evaluation of an Emergency Department Electronic Tracking Board Utility Designed to Optimize Stretcher Utilization - Chisholm, Dirk (Cureus, 2020)
Objectives The primary objective of this study was to evaluate the impact of an electronic tracking board feature encouraging staff to prompt optimal patient location on total stretcher time (TST) amongst patients moved to a chair in an internal emergency department (ED) waiting room. As a secondary objective, we also sought to identify facilitators and barriers to the tool’s use amongst the ED staff. Methods Using an administrative database, a retrospective cohort design was used to compare TST between visits where the tool was used and not used amongst patients relocated from initial assessment space to a chair over an 11.5 month period. A mixed-methods design was used to investigate facilitators and barriers to the tool’s use amongst the ED staff. Response proportions were used to report Likert scale questions; thematic analysis was used to code themes. Results A total of 56,852 patients met the inclusion criteria and were moved to a chair. The tool was used 4,301 times, with “OK for chairs” selected for 3,917/56,852 (6.9%) patients and “not OK for chairs” selected 384/56,852 (0.7%) times. Patient characteristics were similar between both groups. Median interquartile range (IQR) TST amongst patients moved to a chair via the prompt was shorter than when the prompt was not used (148.2 (112.6) mins vs 154.4 (115.4) mins, p = 0.005). A total of 125 questionnaires were completed; 95% of staff were aware of the tool and 70% agreed/strongly agreed the tool could improve ED flow. Commonly reported physician barriers to use were forgetting to use the tool; common nursing barriers were lack of chair space and increased workload. Conclusions Despite low function use, prompt use was associated with reduced TST amongst ED patients relocated to a chair.